The Correlation between Perception of Stigma of HIV/AIDS and Utilization of Voluntary Counseling and Testing and Care, Support and Treatment Polyclinic at Djoelham Hospital, Binjai - Ratih Sufra Rizkani; Surya Utama; Erna Mutiara (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: The health care services for people living with HIV/AIDS (PLWH; hereinafter is referred to as PLWHA) at Polyclinic of Voluntary Counselling and Testing (hereinafter is referred to as VCT) and Care, Support and Treatment (hereinafter is referred to as CST) are not optimally utilized because of the large number of Follow-Up Loss by PLWHA. The utilization of the services in 2018 was only 47% of the determined target of 90%. The objective of this study was to analyze the influence of individual characteristics such as age, sex, education level, marital status, and perception of HIV/AIDS negative stigma on the utilization of health services for HIV/AIDS at Polyclinic of VCT and CST.Subjects and Method: This is a cross-sectional study. The population was all visitors at the Polyclinic who were diagnosed with HIV not later than March, 2018. Sixty eight patients were selected by using total sampling technique. The independent variables consisted of individual characteristics (age, sex, education level, marital status) and perception of HIV/AIDS negative stigma, whereas the dependent variables were the utilization of VCT and CST Polyclinic. The data were collected through questionnaires and were analyzed by multiple logistic regression method.Results: the perception of high negative stigma of HIV/AIDS has led PLWHA to underutilize the health services of VCT and CST Polyclinic (OR= 18.20; 95%CI= 3.89 to 85.19; p< 0.001). The male PLWHA underutilized the health care services at VCT and CST Polyclinic (OR= 4.91; 95%CI=1.19 to 20.23; p= 0.028).Conclusion: the perception of high negative stigma of HIV/AIDS and being a male PLWHA allowed the underutilization of the health services at VCT and CST Polyclinic.Keywords: perception of stigma, HIV, utilizationCorrespondence: Ratih Sufra Rizkani. A Student at Master Program of Public Health Faculty in University of Sumatera Utara, Medan. ratih86rizkani@gmail.com. Mobile: 085261776718Journal of Health Promotion and Behavior (2020), 5(1): 26-34https://doi.org/10.26911/thejhpb.2020.05.01.04